2001
DOI: 10.1353/rhe.2001.0005
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Student-Faculty Interaction In the 1990s

Abstract: This study examined the effects of student-faculty interaction on student satisfaction and on a range of self-reported learning and personal development gains associated with attending college of 5,409 full-time undergraduates from 126 four-year colleges and universities. Findings show that the frequency of student-faculty interaction increased from first year through the senior year. Although its net effects were trivial, such interactions had substantial positive effects on studentsÕ efforts in other educati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
402
3
16

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 525 publications
(443 citation statements)
references
References 24 publications
22
402
3
16
Order By: Relevance
“…Research on these good teaching practices demonstrates that many good teaching practices have a positive relationship with many college outcomes (Cruce, Wolniak, Seifert, & Pascarella, 2006;Edison, Doyle, & Pascarella, 1998;Halpin, 1990;Johnson, 1994;Kuh & Hu, 1999;Kuh & Hu, 2001;Kuh & Vesper, 1997;Pascarella, Cruce, Wolniak, & Blaich, 2004;Pascarella, Edison, Serra Hagedorn, Nora, & Terenzini, 1996;Pascarella, Seifert, & Whitt, 2008;Pascarella, Salisbury, & Blaich, 2011;Pascarella & Terenzini, 2005;Umbach & Wawrzynski, 2005). One main college outcomes that is of interest is evaluating the effect of good teaching practices on student learning.…”
Section: Outcomes Of Good Teaching Practicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Research on these good teaching practices demonstrates that many good teaching practices have a positive relationship with many college outcomes (Cruce, Wolniak, Seifert, & Pascarella, 2006;Edison, Doyle, & Pascarella, 1998;Halpin, 1990;Johnson, 1994;Kuh & Hu, 1999;Kuh & Hu, 2001;Kuh & Vesper, 1997;Pascarella, Cruce, Wolniak, & Blaich, 2004;Pascarella, Edison, Serra Hagedorn, Nora, & Terenzini, 1996;Pascarella, Seifert, & Whitt, 2008;Pascarella, Salisbury, & Blaich, 2011;Pascarella & Terenzini, 2005;Umbach & Wawrzynski, 2005). One main college outcomes that is of interest is evaluating the effect of good teaching practices on student learning.…”
Section: Outcomes Of Good Teaching Practicesmentioning
confidence: 99%
“…Simply having contact with a faculty member appears to have positive results on students' degree aspirations (Astin, 1993;Carter, 1999;Ceja & Rivas, 2010;Endo & Harpel, 1982;Gagnon & Cocolas, 1988;Hearn, 1987;Inozu, 2011;Kim & Sax, 2009;Kuh & Hu, 2001;Pascarella, 1984;Sax, 2001;Sax, Bryant, & Harper, 2005;Varhegyi & Jepsen, 2009). Faculty interactions seem to be important across groups of students.…”
Section: Outcomes Of Good Teaching Practicesmentioning
confidence: 99%
“…This measure is a three-item factor representing students' self-assessment of their current cognitive abilities in three areas: analytical and critical thinking skills, ability to be clear and effective when writing, and ability to read and comprehend academic material (Chronbach's a = .80). College impact research has continuously demonstrated that students' growth in intellectual and cognitive skills is a function of their interaction with faculty (Astin 1993;Endo and Harpel 1982;Kuh and Hu 2001;Pascarella and Terenzini 2005;Sax et al 2005;Strauss and Terenzini 2007;Terenzini and Pascarella 1980;Volkwein et al 1986). Further, using the 2006 UCUES data, Kim and Sax (2009) confirmed the positive effects of student-faculty interaction on students' gains in critical thinking and communication skills.…”
Section: Student-level Variablesmentioning
confidence: 99%
“…The current study attempts to improve our understanding of the disciplinary effects of college by examining differential effects of student-faculty interaction on students' growth in selfassessed cognitive skills across academic majors. General cognitive or intellectual abilities and skills are among the most desired student educational outcomes Terenzini 1991, 2005) and have been considered some of the key byproducts of student-faculty interaction (Astin 1993;Endo and Harpel 1982;Kuh and Hu 2001;Pascarella and Terenzini 2005;Sax et al 2005;Strauss and Terenzini 2007;Terenzini and Pascarella 1980;Volkwein et al 1986). Through the use of multilevel modeling, this study seeks to answer the following two research questions: (1) Is the relationship between student-faculty interaction and student cognitive skills development different across academic majors?…”
mentioning
confidence: 99%
“…A major asset of undergraduate research programs or conducting research with faculty is the potential to enhance positive student-faculty interaction and mentorship. Fostering student-faculty interaction is particularly important to keeping URM students engaged during their undergraduate years because these interactions are linked to numerous positive cognitive and affective outcomes, including academic achievement, educational aspirations, student self-concept, and persistence (Astin 1977(Astin , 1993Chickering 1969;Kuh 1995;Kuh and Hu 2001;Pascarella 1985;Pascarella andTerenzini 1977, 1978;Spady 1970).…”
Section: Research and Theory Guiding The Studymentioning
confidence: 99%